Is Work Bad for Health? The Role of Constraint vs Choice - Andrea Bassanini; Eve Caroli (Institute for the Study of Labor (IZA), 2014)
This paper reviews the literature on the impact of work on health. We consider work along two dimensions: (i) the intensive margin, i.e. how many hours an individual works and (ii) the extensive margin, i.e. whether an individual is in employment or not, independent of the number of hours worked. We show that most of the evidence on the negative health impact of work found in the literature is based on situations in which workers have essentially no control (no choice) over the amount of work they provide. In essence, what is detrimental to health is not so much work per se as much as the gap which may exist between the actual and the desired amount of work, both at the intensive and extensive margins.
Keywords: I10; I31; J22; J28; 330; health; work; retirement; hours worked; job loss; individual choice